2021
DOI: 10.1038/s41531-021-00158-x
|View full text |Cite
|
Sign up to set email alerts
|

Timing variability and midfrontal ~4 Hz rhythms correlate with cognition in Parkinson’s disease

Abstract: Patients with Parkinson’s disease (PD) can have significant cognitive dysfunction; however, the mechanisms for these cognitive symptoms are unknown. Here, we used scalp electroencephalography (EEG) to investigate the cortical basis for PD-related cognitive impairments during interval timing, which requires participants to estimate temporal intervals of several seconds. Time estimation is an ideal task demand for investigating cognition in PD because it is simple, requires medial frontal cortical areas, and rec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
115
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
3

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(148 citation statements)
references
References 68 publications
13
115
1
Order By: Relevance
“…All intraoperative research procedures were approved by the UI IRB (#201402730). All patients were tested on levodopa as our past work has shown that levodopa does not reliably modulate midfrontal ~4 Hz rhythms (Singh et al, 2018(Singh et al, , 2021. Levodopa-equivalent doses (LEDD) are presented in Table 2.…”
Section: Participantsmentioning
confidence: 99%
“…All intraoperative research procedures were approved by the UI IRB (#201402730). All patients were tested on levodopa as our past work has shown that levodopa does not reliably modulate midfrontal ~4 Hz rhythms (Singh et al, 2018(Singh et al, , 2021. Levodopa-equivalent doses (LEDD) are presented in Table 2.…”
Section: Participantsmentioning
confidence: 99%
“…Indeed, PD patients can have specific challenges in learning (Frank et al., 2004; Nieuwboer et al., 2009) and in performing functions for which they have extensive experience (Uc et al., 2006, 2007). PD patients have impairments in interval timing (Malapani et al., 1998, 2002; Merchant et al., 2008; Singh et al., 2021). In animal models, dopamine depletion can profoundly change striatal firing patterns and promote aberrant synchrony that is not entirely normalized by dopamine agonists (Alberico et al., 2017; Jáidar et al., 2019; Lara‐González et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Potential limitations of the interval timing cognitive task, lower-limb pedaling motor task, and both tasks-related cortical EEG have been discussed extensively in our prior reports (Singh et al, 2020;Singh et al, 2021) since cortical and cerebellar EEG data were collected from the same participants and under similar conditions. In addition, there were several limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…We also recruited 5 PD patients to collect cerebellar EEG and electromyography (EMG) signals from the nearby muscles during resting and body actions. In our previous reports, all clinical details of the patients and control groups who participated in the cognitive task (Singh et al, 2021) and lower-limb pedaling motor task (Singh et al, 2020) are described and have been summarized in Table 1. All participants performed the interval timing cognitive and lower-limb pedaling motor tasks with levodopa medication.…”
Section: Participantsmentioning
confidence: 99%